Model Dependant And Statistical Approaches To Study Release Kinetics Of Meloxicam Release Matrix Tablets - MONICA SHARMA; Dr. USHA CHOUHAN (International Journal of Pharma and Bio Sciences, 2015)
In this paper various mathematical and model dependant approaches were applied to understand the kinetics of drug release of Meloxicam release matrix tablets. In-vitro drug release studies of nine formulations were carried out. ANOVA technique was used to compare the dissolution profile of the drug. Various model dependant methods like Zero-order, first-order, Higuchi, Hixson-Crowell, and Korsmeyer model were used to estimate the kinetics of drug release. For selecting the most appropriate model the goodness-of-fit test, lowest sum of squares residual and square of correlation constant was used. A mathematical approach was used to estimate the deviation in Area Under the Curve (AUC) between predicated and observed dissolution data of the drug. The optimal batch had the lowest difference in percent deviation of AUC at each point. Finally, unpaired t test was used to compare the dissolution profile of the optimal batch with that of the other batches.